2011
DOI: 10.1038/cmi.2011.24
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric flagellin expressed by Salmonella typhimurium induces an ESAT-6-specific Th1-type immune response and CTL effects following intranasal immunization

Abstract: The flagellin component FliC of Salmonella typhimurium is capable of activating the innate immune system via specific interactions with TLR5 and can also act as a carrier of foreign antigen to elicit antigen-specific immune responses. Thus, we constructed an attenuated Salmonella strain SL5928(fliC/esat) expressing chimeric flagellin that contained the ESAT-6 antigen coding sequence of Mycobacterium tuberculosis inserted into the highly variable region of the Salmonella flagellin coding gene fliC i . The chime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…While the first group might facilitate a productive DC-T cell interaction, the second group could play an important immunomodulatory role in intraclonal competition of T cells (159). Similarly, CD4 T cell-released exosomes were found to inhibit CTL responses and antitumor immunity (160). Yet, others observed that T cell-derived EVs could activate cognate B cells (37,155), possibly through transfer of miRNA (5).…”
Section: T Cell-derived Extracellular Vesiclesmentioning
confidence: 99%
“…While the first group might facilitate a productive DC-T cell interaction, the second group could play an important immunomodulatory role in intraclonal competition of T cells (159). Similarly, CD4 T cell-released exosomes were found to inhibit CTL responses and antitumor immunity (160). Yet, others observed that T cell-derived EVs could activate cognate B cells (37,155), possibly through transfer of miRNA (5).…”
Section: T Cell-derived Extracellular Vesiclesmentioning
confidence: 99%
“…If ferritin emerged in supernatant, it was seemed as soluble expressed, such as flagellin. 10 , 26 If ferritin was in precipitate, it was seemed as aggregated expressed, such as VP1. 15 , 27 So, when little scale tests were did to see the solubility of one protein expressed in E coli in our laboratory, bacteria in LB were brought to do the ultrasonic crack directly for operating convenience usually.…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al [ 176 ] reviewed all the studies using flagellin as an adjuvant. The simplest method is administering it with an antigen; this simple method successfully induces a mucosal immune response essential in protecting against respiratory and gastrointestinal infections [ 177 , 178 ]. Many studies have been carried out, especially regarding the role of flagellin as an adjuvant in influenza vaccines [ 179 , 180 , 181 , 182 , 183 ].…”
Section: Immune Potentiatorsmentioning
confidence: 99%
“…In these studies, flagellin from Salmonella typhimurium was used combined with different influenza antigens, among which inactivated PR8 influenza virus (IPR8), HA(H5N1), and avian influenza virus (AIV) H5N1, and for each of them, a robust immune response (especially mucosal with IgA production) was obtained. Flagellin can also be successfully modified in order to obtain chimeric flagellins or complexes of flagellin antigen in live attenuated bacteria such as Mycobacterium tuberculosis [ 178 ], Vibrio cholerae [ 184 ], Streptococcus pyogenes [ 185 ], Listeria monocytogenes [ 186 ] and enterotoxigenic Escherichia coli (ETEC) [ 187 , 188 ]. Moreover, the production of recombinant flagellin-antigen fusion proteins has been used in animal models as adjuvanted vaccines both for infectious diseases and cancers [ 176 ].…”
Section: Immune Potentiatorsmentioning
confidence: 99%